Penerapan Sistem Good Manufacturing Practices (GMP) pada UD Sae Food - Lisah Alizah; Hamzah Robbani; Nur Sodik (JUDICIOUS, 2022)
The purpose of this study was to determine the application of Good Manufacturing Practices (GMP) in the production of UD Sae Food's kwetiau food. This research method is descriptive qualitative using a case study approach. The data obtained are primary data. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of observations and interviews at UD Sae Food show that there are still 5 aspects of GMP that have serious deviations. These aspects include machinery and equipment, process supervision, employees, sanitation facilities, maintenance and sanitation facilities. Improvements to the condition of these aspects need to be followed up immediately in order to meet the requirements of the GMP standard according to the Minister of Industry of the Republic of Indonesia No. 75/M-IND/PER/7/2010 concerning Guidelines for Good Processed Food Production. In addition, it is seen that there are still many employees who violate company rules, namely not using complete PPE during the production process. Based on the results of observations made, there are 4 aspects that have not been implemented by UD Sae Food, namely laboratory aspects, documents and records, training and implementation of guidelines. This aspect has not been implemented by UD Sae Food, so it is necessary to improve this aspect in order to meet GMP standards. However, there are 9 aspects that are considered to have no deviations and do not pose a risk to the food safety quality of the product, namely aspects of location, building, materials, packaging, labels and product descriptions, storage, and transportation.